2017
DOI: 10.2320/matertrans.m2016382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α Phase Nucleating at Transition Phase and Dislocation on Mechanical Properties in Metastable β Titanium Alloy Ti-6.8Mo-4.5Fe-1.5Al

Abstract: Effects of α phase nucleating at a transition phase and dislocation on mechanical properties in a metastable β titanium alloy, Ti-6.8Mo-4.5Fe-1.5Al(mass%), were investigated. Tensile test and optical, scanning, and transmission electron microscopy were used. Two-step aging promoted the precipitation of a ne α phase in grain interiors because the α phase nucleated at a transition phase of β ′ . A precipitation-free zone appeared at rst, but nally disappeared during aging. A specimen that included the precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Quazi et al [41] observed precipitate free zones, presumably due to grain boundaries ac ng as sinks for oxygen in samples aged at increased aging temperature in high-oxygen-enriched Ti-Nb alloys. Mantri et al [42] and Sakamoto et al [43] observed an improved duc lity in samples forming precipitate free zones. Precipitate free zones are not typical for Ti-1023, however Duerig et al [4] described a thick layer of grain boundary alpha forming at high aging temperature 680°C a�er 2000min in an alloy with an oxygen content 0.15 wt pct.…”
Section: Current Situationmentioning
confidence: 93%
“…Quazi et al [41] observed precipitate free zones, presumably due to grain boundaries ac ng as sinks for oxygen in samples aged at increased aging temperature in high-oxygen-enriched Ti-Nb alloys. Mantri et al [42] and Sakamoto et al [43] observed an improved duc lity in samples forming precipitate free zones. Precipitate free zones are not typical for Ti-1023, however Duerig et al [4] described a thick layer of grain boundary alpha forming at high aging temperature 680°C a�er 2000min in an alloy with an oxygen content 0.15 wt pct.…”
Section: Current Situationmentioning
confidence: 93%